Towards an Assay for Liposome-based Vaccine Uptake by Dendritic Cells - Norling, Karin (My University, 2014)
There are rising concerns that an inevitable Influenza A outbreak of pandemic proportions will spread at a previously unmatched rate due to the nature of our modern travel habits. It is therefore becoming increasingly urgent to develop effective, safe and easily administered vaccines suitable for use in a pandemic situation. Recently, increasing focus has been laid on the development of nanocarriers for vaccination compounds with liposomes being promising carrier candidates. Liposomes are almost endlessly customizable which makes finding the optimal formulation a difficult task. Furthermore, little is currently known about how the rate and mode of uptake of a vaccine formulation by immune cells correlates to the induced immunity, and improved knowledge of this process would allow rationalization of the development of vaccine formulations. The aim of this master’s thesis was therefore the development of an assay for the characterization and quantification of uptake of liposomes functionalized with an influenza vaccine compound candidate, by dendritic cells. To this end, total internal reflection fluorescence (TIRF) microscopy, epifluorescence microscopy and single particle tracking was applied and different assay approaches were evaluated. TIRF microscopy was used to probe the movement of cell-bound, fluorescently labelled liposomes at the basal membrane. The results revealed that the movement of individual liposomes was largely confined, or possibly directed. However, no uptake events by membrane fusion or by endocytosis could be clearly identified in these experiments. Epifluorescence microscopy was used in an attempt to quantify the overall liposome uptake by recording the change over time in the number of cell-bound liposomes. However, no decrease in the number of attached liposomes could be established. The work performed in this master’s thesis represents the first step towards the establishment of an assay for the study of uptake of functionalized liposomes by dendritic cells and gives useful practical insight into the possibilities and pitfalls of the set-up.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Bioteknologi med applikationer på växter och djur; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Agricultural Biotechnology